Manejo de enfermería en gestantes con anemia ferropénica - Johnatan Paul, Inguillay Guagcha (2023)
ABSTRAC According to the World Health Organization (WHO), iron deficiency anemia is defined as a common condition during pregnancy, due to increased iron needs due to the expansion of the maternal erythrocyte mass, fetal and placental growth. If not prevented or treated in time, iron deficiency anemia is associated with an increased risk of preterm birth, low birth weight, and other complications. This bibliographic review entitled: Nursing management in pregnant women with iron deficiency anemia, was prepared considering the activities carried out by nursing staff in health units; The objective of the present study was to determine the main risk factors that lead to the appearance of iron deficiency anemia in pregnant women, as well as the symptoms and at the same time establish nursing care with the use of the NIC taxonomy; To this end, information was reviewed and compiled in different documents published in scientific bases such as: Dialnet, Scielo, Redalyc, Elsevier, Google Scholar; In the same way, the following web pages were consulted: World Health Organization (WHO), Pan American Health Organization (PAHO), Ministry of Public Health of Ecuador (MSP), World Health Assembly (WHA), National Institute of Statistics and Censuses (INEC), of which 99 bibliographic sources were taken as a sample, and 49 were used for the triangulation and analysis process. Based on the results, it was established that nursing plays an important role in the care and attention of pregnant women with iron deficiency anemia, with the purpose of guiding and helping to make responsible decisions; Among its interventions are nutritional counseling considering dietary beliefs, supplementation with micronutrients such as iron orally, parenterally, and promoting healthy practices, recognizing certain aspects that influence the treatment of their disease. Keywords: iron deficiency anemia, care, pregnant women, nursing education.